2006
DOI: 10.1007/s00251-006-0126-1
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the mast cell chymase locus over the past 200 million years of mammalian evolution

Abstract: The acidic granules of natural killer (NK) cells, T cells, mast cells, and neutrophils store large amounts of serine proteases. Functionally, these proteases are involved, e.g., in the induction of apoptosis, the recruitment of inflammatory cells, and the remodeling of extra-cellular matrix. Among the granule proteases are the phylogenetically related mast cell chymases, neutrophil cathepsin G, and T-cell granzymes (Gzm B to H and Gzm N), which share the characteristic absence of a Cys(191)-Cys(220) bridge. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 51 publications
1
50
1
Order By: Relevance
“…The results strongly suggest that, during evolutionary diversification, the rodent ␣-chymases have separated relatively recently from other chymases, whereas neutrophil and pancreatic elastases have evolved independently of chymases. Thus, despite the elastolytic specificity, comparison of substrate-binding sequence regions of chymases and other serine proteases agree with an earlier hypothesis that rodent ␣-chymases are more closely related to chymase-like enzymes than to elastases (39,41,43).…”
supporting
confidence: 72%
See 3 more Smart Citations
“…The results strongly suggest that, during evolutionary diversification, the rodent ␣-chymases have separated relatively recently from other chymases, whereas neutrophil and pancreatic elastases have evolved independently of chymases. Thus, despite the elastolytic specificity, comparison of substrate-binding sequence regions of chymases and other serine proteases agree with an earlier hypothesis that rodent ␣-chymases are more closely related to chymase-like enzymes than to elastases (39,41,43).…”
supporting
confidence: 72%
“…An extensive comparison of crystal structures within the trypsin family of serine proteases has revealed that specificity-conferring residues are most often located at positions 189, 216, and 226 (40,41,44 diminish the space available for a P1 substrate side chain. In trypsin, the negatively charged Asp 189 , which forms a direct ionic interaction with the basic P1 residues Lys or Arg, at the bottom of the S1 pocket is the main determinant for trypsinlike specificity (40 , and Val 216 in all known rodent ␣-chymases form an easily identifiable triplet that can be used in the prediction of elastolytic specificity for any novel chymase-like sequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monodelphis domestica, the South American gray short-tailed opossum, is the first metatherian mammal to have its genome sequenced (Mikkelsen et al, 2007). Evolutionary (Gallwitz et al, 2006;Belov et al, 2007;Goodstadt et al, 2007) and functional (Ek et al, 2006;Freyer et al, 2007) studies have been extensively conducted, but morphological studies are sparse (Sanchez-Villagra and Maier, 2003;Kitchener et al, 2006). Because of its size similarities to mouse and rat, Monodelphis domestica is also emerging as a useful tool for preclinical studies (Chan et al, 2002).…”
Section: Multi-species Data Can Be Quantitatively Compared Using Microctmentioning
confidence: 99%